Ṭuruq Ta’līm Kutub at-Turāṡfi al-Ma’had al-Islāmīat-Taqlīdīal-Madīnah ad-Dīniyyah Aceh Dār al-HudāPaloh Gadeng Syimāliyyah - Syahrizal Syahrizal (Center for Research and Development of Religious Literature and Heritage, 2018)
This paper describes the method used by the teacher in teaching the book of monotheism, the obstacles faced by the teacher and the solution, finding the weaknesses and strengths of the teaching method, and knowing the possibility of developing the teachingmethod of the book in Darul Huda Paloh Gadeng North Aceh traditional Islamic School. Based on the results of field research using interview, observation and documentation techniques, the research findings are the methods used by the teacher in the teaching of the books al-'aqīdah al-islāmiyah, tījan ad-durari, and hud hudiin general, namely the method of reading, translation, lecture, question and answer, repetition, and conclusion.The teacher's constraints in the use of teaching methods in each book of monotheism are different. This is due to differences in the ability of students to learn the teaching of the book al-'Aqīdah al-Islāmiyah, Tījan ad-Durari,and Hud Hudi. Those differences have their own advantages and disadvantages. The methods of teaching the tauhid book in the traditional Islamic School in Aceh still need development and renewal in accordance with the times and technological advances.